2020
DOI: 10.1016/j.ijmecsci.2019.105331
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the periodic V-peeling behavior of elastic tapes applied to thin compliant substrates

Abstract: In this paper, we investigate the periodic peeling behavior of opposing symmetric peeling fronts involving an elastic tape peeled off from a deformable substrate of finite thickness, backed onto a rigid foundation.We treat the problem by means of an energetic formulation, and we found that, depending on the values of the initial detached length l, substrate thickness h, and peeling periodicity λ, the translational invariance of the peeling process is lost and restored, as the elastic interaction between the pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Eq. (10) shows that δL P is a non-conservative term, which vanishes in the case of purely elastic material, i.e., G O (x, v) = 0 [26,29,51]. Moreover, it is worth noting that this term does not represent the amount of energy dissipated within the bulk viscoelastic material.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eq. (10) shows that δL P is a non-conservative term, which vanishes in the case of purely elastic material, i.e., G O (x, v) = 0 [26,29,51]. Moreover, it is worth noting that this term does not represent the amount of energy dissipated within the bulk viscoelastic material.…”
Section: Formulationmentioning
confidence: 99%
“…Understanding the effect of adhesion in sliding contacts of polymeric rubber-like materials is of crucial importance in a large number of engineering and industrial applications, as in Micro-Electro-Mechanical systems (MEMs) [1,2,19], medical applications [3,4], seals [5,6], biological and bio-inspired systems [7][8][9][10][11][12], protective coatings [13,14], tire-road frictional behavior [15,16], windscreen wipers [17], touchscreens [18]. Controlling adhesion is fundamental, as the adhesive effect might be desirable, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…( 1) takes into account both the elastic energy stored in the tape, and the bulk energy dissipation occurring due to viscoelastic creep in the detached strip. Since we focus on thin tapes, we can neglect the bending contribution to W I (see also Refs [54,55]). Hence we write…”
Section: Stuck Interfacementioning
confidence: 99%
“…Indeed, several studies have identified this mechanism as one of the sources of the superior adhesive performance of the geckos [45][46][47], insects [48,57] and frogs [49], beside the well investigated effect of the hierarchical nature of the attachment pads of these animals [50][51][52]. Moreover V-shaped peeling configuration observed in such biological systems [53][54][55][56] plays also a role in facilitating the ability of climbing animals to easily switch between firm attachment and effortless detachment. The resulting peeling force arises due to the combination of three main physical mechanisms [59]: (i) tape pre-strain due to partial sliding occurring during detachment [60,61]; (ii) the friction losses associated with the slip at the interface [58]; (iii) the viscous dissipation in the bulk of the material [62].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, a constantly rising interest on the tribological behavior of thin coatings has been reported in the last decades. Indeed, besides the theoretical [4][5][6][7][8][9][10][11], numerical [12][13][14][15][16][17] and experimental [18][19][20][21] studies focusing on contact problems where both bodies can be treated as half-spaces (or semi-infinite), detailed investigations have been also devoted to the case of interfaces involving thin bodies [22][23][24][25][26] leading to qualitatively different results with respect to half-space solutions.…”
Section: Introductionmentioning
confidence: 99%